(3JQGcjH GdCfhGQ (B((3aj GdUfGYI(B)s - (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s ((3CMeO Hf Ydj Hf MeRI GdMfHdj s)
(3ChdgG (B:s
(3hHYO abO HYKfj GdRGaI Ydi eYGTQ ENhGfj haQW GdeMHI s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg JYGdi hYhfg hMSf Jhajbg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B394s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUfGYI hGdCWYeIs